SMEs’ MARKETING PERFORMANCE: THE ROLE OF ENTREPRENEURAL ORIENTATION AND NETWORKING CAPABILITY - Wahyuningsih Wahyuningsih; Elimawaty Rombe; Maskuri Sutomo (JURNAL DIMENSI, 2023)
Marketing performance have attracted many practitioners and academics in the last few years, specifically for SMEs. This research aims to investigate relationhsips among entrepreneurial orientation, networking capabilities, and marketing performance, This is a descriptive research design using online survey. Data were collected employing Google online survey application through social media to SMEs in Indonesia Structural Equation Modeling using Partial Least Square (PLS) has been utilized to examine proposed hypotheses. The results show that entrepreneurial orientation positively influences marketing performance. Further, entrepreneurial orientation performs a positive and significant effect on networking capabilities. Correspondingly, networking capability has a positive and significant effect on marketing performance. The findings of this study contribute to the body of knowledge in marketing literature by enlarging the linkage between entrepreneurships and social interactions in building relationships. Practical implications for managers, owners, and entrepreneurs of SMEs are acknowledged.